STUDENTS’ QUESTIONNAIRE AS AN INTEGRAL METHOD OF EDUCATIONAL WORK OF A CURATOR AT HIGHER EDUCATIONAL ESTABLISHMENT - Ерстенюк, А. М.; Князевич-Чорна, Т. В.; Ванджура, І. Ю.; Мерена, Р. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The article analyzes the results of students’ questionnaires of SHEE “Ivano-Frankivsk National Medical University” on first-year students’ motivation when choosing a medical educational institution, the process of their adaptation, the interest of second-year and fourth-year students in the educational process, their ideas about successful completion of the Step-1 exam. Such systemic monitoring has a positive impact on the organization of educational work and the educational process of SHEE.